PLEISTOCENE PALYNOLOGY OF THE WAIPONA BASIN, PAPUA - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2008)
The Pleistocene sediment from a single well drilled on the back bone of Papua provides good pollen recovery which shows the mixture of the Australian and Asian elements. The well drilled the sediment more than 3000 meter deep which is mostly assigned to Pleistocene age. Only small part of the basal section belongs to Pliocene age. In order to obtain accurate interpretation, the age interpretation is also defined using other disciplines including foraminifera and nannoplankton. The Australian affinity appears as an origin since this island has derived from the Australian continent. On the other hand, the existence of Asian palynomorphs within the studied sediment indicates the dispersal of Asian flora into East Indonesia following the arrival of the Australian plates at about the end of Oligocene. The Asian taxa then migrated to the land mass of New Guinea which rose above sea level from about Middle Miocene onward. In the studied section, shallow marine sediment in the upper interval contains sufficient palynological assemblages which clearly indicate climatic changes from dry or seasonal to wet climate as reflected on the changes of the proportion of dry/ seasonal and wet climate indicators. Unfortunately, due to low pollen recovery, the climate condition of the lower interval can be hardly interpreted. This could have happened because the sediment of the lower interval was deposited in deep marine environment, which was situated far away from the pollen sources in the continent.